The Position of Children as a Result of Marriage Cancellation of Inbreeding - Hasnadewi, Nada; Sulistyarini, Rachmi; Chanifah, Nur (IJBLE Scientific Publications Community Inc., 2024)
Human life is inherently paired. So that humans get married. Marriage is a legal and regular offspring connector so as to avoid mixing offspring or bloodline. inbreeding is clearly prohibited in the Marriage Law. The Compilation of Islamic Law also regulates the prohibition of marriage. Then there is a cancellation of marriage from inbreeding. As a result of the cancellation of marriage, the position of children from the cancellation of marriage arises. In terms of the Marriage Law related to the consequences of marriage cancellation in Article 28, the cancellation of marriage begins after a decision from the Court that has permanent legal force and is valid from the time of the marriage. The decision regarding the cancellation of marriage states that it does not apply retroactively to children born from the marriage. This creates uncertainty regarding the position of children from the cancellation of marriage for inbreeding. A marriage is declared invalid according to law and religion if it violates the provisions regarding the conditions or prohibitions in marriage. So can these provisions also apply to the cancellation of marriage for inbreeding. As well as legal protection for the fulfilment of children's rights due to marriage cancellation of inbreeding.